2019
DOI: 10.3389/fonc.2019.00370
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hepatitis B Virus Infection to the Aggressiveness of Primary Liver Cancer: A Clinical Epidemiological Study in Eastern China

Abstract: Background and aims: The contribution of hepatitis B virus (HBV) infection to the aggressiveness of primary liver cancer (PLC) remains controversial. We aimed to characterize this in eastern China. Methods: We enrolled 8,515 PLC patients whose specimens were reserved at the BioBank of the hepatobiliary hospital (Shanghai, China) during 2007–2016. Of those, 3,124 who received primary radical resection were involved in survival analysis. A nomogram was constructed to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 43 publications
1
56
1
Order By: Relevance
“…Chronic HBV infection in China has been considered to be the most common factor in the etiology of liver cancer and a major contributor to its development . Our study showed that the proportion of liver cancer caused by hepatitis B was approximately 60%, which is significantly lower than previous reports . This difference might be partly explained by that we used the nationwide data instead of the regional data used in previous studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Chronic HBV infection in China has been considered to be the most common factor in the etiology of liver cancer and a major contributor to its development . Our study showed that the proportion of liver cancer caused by hepatitis B was approximately 60%, which is significantly lower than previous reports . This difference might be partly explained by that we used the nationwide data instead of the regional data used in previous studies.…”
Section: Discussioncontrasting
confidence: 70%
“…30 Our study showed that the proportion of liver cancer caused by hepatitis B was approximately 60%, which is significantly lower than previous reports. 8,31 This difference might be partly explained by that we used the nationwide data instead of the regional data used in previous studies. To combat HBV, the Chinese government initiated a national immunization program to address the HBV epidemic.…”
Section: Discussionmentioning
confidence: 97%
“…Hepatocellular carcinoma (HCC), the major pathological type of liver cancer, is still a leading cause of cancer‐related death worldwide . In Asia and Africa, chronic hepatitis B virus (HBV) infection is the major cause of HCC development . Although it has been suggested that several factors, including the repeated inflammation mediated by immune reactions against the virus, the integration of HBV DNA into the host genome and the virus‐encoded oncoproteins (HBx and preS2/S proteins), are responsible for the development of HCC induced by HBV infection, the molecular mechanisms of hepatocarcinogenesis caused by HBV infection are still not well understanding, and no effective agents have been developed for the treatment of HBV‐related HCC.…”
Section: Introductionmentioning
confidence: 99%
“…1 In Asia and Africa, chronic hepatitis B virus (HBV) infection is the major cause of HCC development. [2][3][4] Although it has been suggested that several factors, [5][6][7] including the repeated inflammation mediated by immune reactions against the virus, the integration of HBV DNA into the host genome and the virus-encoded oncoproteins (HBx and preS2/S proteins), are responsible for the development of HCC induced by HBV infection, the molecular mechanisms of hepatocarcinogenesis caused by HBV infection are still not well understanding, and no effective agents have been developed for the treatment of HBV-related HCC. Hence, it is extremely important to discover novel molecules involved in the carcinogenesis of HBV-associated HCC and offer the possibility of improving therapeutic approaches for HCC with HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic infection of hepatitis B virus (HBV) is the major cause of hepatocellular carcinoma (HCC) globally [1] . In Eastern China, chronic HBV infection contributes to 87.5% of HCC whereas chronic hepatitis C virus (HCV) infection contributes to 1.7% [2] . The mortality of HCC has increased in Europe and America over recent decades [3] .…”
mentioning
confidence: 99%